Endocardial role in arrhythmias induced by acute ventricular stretch and the involvement of Purkinje fibres, in isolated rat hearts - Miriam Hurley; Sarbjot Kaur; Richard Walton; Amelia Power; Michel Haïssaguerre; Olivier Bernus; Marie-Louise Ward; Ed White (Current Research in Physiology, 2023)
Purkinje fibres (PFs) play an important role in some ventricular arrhythmias and acute ventricular stretch can evoke mechanically-induced arrhythmias. We tested whether PFs and specifically TRPM4 channels, play a role in these mechanically-induced arrhythmias. Pseudo-ECGs and left ventricular (LV) activation, measured by optical mapping, were recorded in isolated, Langendorff-perfused, rat hearts. The LV endocardial surface was irrigated with experimental agents, via an indwelling catheter. The number and period of ectopic activations was measured during LV lumen inflation via an indwelling fluid-filled balloon (100 μL added over 2 s, maintained for 38 s). Mechanically-induced arrhythmias occurred during balloon inflation: they were multifocal, maximal in the first 5 s and ceased within 20 s. Optical mapping revealed activation patterns indicating PF-mediated and ectopic focal sources. Irrigation of the LV lumen with Lugol solution (IK/I2) for 10s reduced ectopics by 93% (n = 16, P < 0.001); with ablation of endocardial PFs confirmed by histology. Five min irrigation of the LV lumen with 50 μM 9-Phenanthrol, a blocker of TRPM4 channels, reduced ectopics by 39% (n = 15, P < 0.01). Immunohistochemistry confirmed that TRPM4 was more abundant in PFs than myocardium. Our results show that the endocardial surface plays an important role in these mechanically-induced ectopic activations. Ectopic activation patterns indicate a participation of PFs in these arrhythmias, with a potential involvement of TRPM4 channels, shown by the reduction of arrhythmias by 9-Phenanthrol.